Thunder rose eaudiobook - Nolen, Jerdine (Recorded Books Inc., 2017)
Born during a storm, the first thing Rose MacGruder does is grab a bolt of lightning and roll it into a ball. Soon she is staking fences, driving cattle, and lassoing hooligans. But when she gets caught between two tornadoes, her mighty strength might not be enough to help her survive. Award-winning author Jerdine Nolen's tale is a refreshing piece of American folklore.